If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 5) + 6(x + -1) = -10 Reorder the terms: 7(5 + x) + 6(x + -1) = -10 (5 * 7 + x * 7) + 6(x + -1) = -10 (35 + 7x) + 6(x + -1) = -10 Reorder the terms: 35 + 7x + 6(-1 + x) = -10 35 + 7x + (-1 * 6 + x * 6) = -10 35 + 7x + (-6 + 6x) = -10 Reorder the terms: 35 + -6 + 7x + 6x = -10 Combine like terms: 35 + -6 = 29 29 + 7x + 6x = -10 Combine like terms: 7x + 6x = 13x 29 + 13x = -10 Solving 29 + 13x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-29' to each side of the equation. 29 + -29 + 13x = -10 + -29 Combine like terms: 29 + -29 = 0 0 + 13x = -10 + -29 13x = -10 + -29 Combine like terms: -10 + -29 = -39 13x = -39 Divide each side by '13'. x = -3 Simplifying x = -3
| 3.9-30= | | X-4-20x=-2 | | 6x^2-4x-20=14 | | X+3*4= | | X^2+13x+36=36 | | 54=27x | | 2x-4+12=8(x+1-2x) | | 45/(4+1)=18-49*(3+2) | | 5x+y+3=3 | | 4t^2-4t-8=0 | | 2y+x=110fory | | c=5a+b | | 2(x+6)=4(x+2.6) | | x-.4=.4x | | 45/(4+1)= | | -4(5a-10)=0 | | f(x)=27x | | 60c-54c+108=0 | | 2x-4+12=8(x+1)-2x | | x^2+169-12=0 | | -5+7(x+6)=x+37 | | (x+2)4=8 | | 15x^2+16x+7=0 | | 33-(x+5)=8x-8 | | d=18+-27 | | (4b+3c)(5b+2c)=0 | | 200=2x+100 | | 2x+5x-9=5 | | 5(d+1)-3=32 | | 5x+4-4X=12whatisx | | -3(x-9)-3(3x-5)-7x= | | 0.5(2x-6)+3=8(0.3x-5) |